The Applying of Asking Stage Strategy to Teach Reading Comprehension - Maria Ramasari; Ardayati Ardayati (English Education Study Program Faculty of Teacher Training and Education, 2022)
Abstract The main problem of this study was: is it significantly effective to teach reading comprehension by applying of asking stage strategy. Therefore, the main objective of this study was to find out whether or not it is significantly effective to teach reading comprehension by applying of asking stage strategy to the seventh grade students. Method used was pre-experimental method with one group pre-test post-test design. Population was all of the seventh grade students at SMP Negeri 5 Lubuklinggau which consisted of 8 classes with 261 students. Sample of this study was taken by using cluster random sampling, with number of sample 35 students. Data were collected through test consisting 20 items of multiple choices. The obtained data were analyzed through three techniques: 1) Individual Score, 2) conversion of score range, 3) the matched t-test. There were three major findings in this study, they are: (1) students’ mean score in the pre-test was (67.14), (2) students’ mean score in the post-test was (79.29), and (3) the result of matched t-test calculation should that t obtained was (6.75), which is higher than 1.697 as the critical value of the t table for degree of freedom 34 (35-1) with 95% significant level for one-tailed test. It can be concluded that the null-hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The fact shows that it was significantly effective to apply asking stage strategy for teaching reading comprehension for the seventh grade students at SMP Negeri 5 Lubuklinggau.